Pengaruh Corporate Social Responsibility, Dividend Policy, dan Leverage terhadap Nilai Perusahaan - Fitriani, Desi; Novera Kristianti Maharani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to examine how the value of food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023 is influenced by CSR, Dividend Policy, and leverage. Tobin's Q Tobin was used to determine the value of the company in this study, and Debt to Equity Ratio (DER), Corporate Social Responsibility (CSR), Dividend Payout Ratio (DPR) were used as independent variables. Using quantitative methodology and multiple linear regression analysis, this study examined 84 observations from 28 selected business actors using purposive sample strategy. However, 18 data points were eliminated because they were identified as extreme data. The elimination was carried out to maintain the validity of the results, avoid estimation bias, and ensure that the multiple linear regression model met the classical assumptions more accurately, leaving 66 companies as the objects of the study. The analysis findings show that, in contrast to CSR and leverage, Dividend Policy has a positive and substantial impact on the value of the company. The findings indicate that the distribution of dividends is an important financial signal for investors in assessing the company's prospects, while the implementation of CSR and debt-based funding structures have not been the main determinants in assessing the company's value. The practical implications of this study are the importance of Dividend Policy consistency as a strategy to increase corporate value, as well as the need to strengthen the integration of CSR programs in corporate strategies to create more sustainable value in the future.